Green art practice: elicitation of the primary colours from the local plants for the art of painting / Siti Rafeah Iskandar - Iskandar, Siti Rafeah (2022)
Plant-based colour manufacturing is an alternative to synthetic colour creation, which produces waste and pollutes the environment. Plants have been used as a primary source of natural dyes in food production, woven fabrics and textiles, and even cosmetics and beauty substances since ancient times. Telang flowers produce blue hue, turmeric produces yellow colour, and roselles’ natural colour is red. Primary colours such as red, blue, and yellow cannot be created by mixing with other colours, however, secondary and subsequent colours can be created by mixing together a few of the primary colours. The purposes of this research are to learn about (1) the process of producing colours from traditional extracts of roselles, turmeric, and telang flowers, (2) the colours produced on drawing paper when the plant extracts are mixed with Arabic gum, glycerin, kaolin, rice flour, and water as solvents, and (3) the potential of the colours produced by roselles, telang flowers, and turmeric as natural dyes that can be used to create paintings.